The Effect of Self-Efficacy on Academic Performance: The Mediating Role of Adaptation and Motivation in Seafaring Students - Hanik, Kumila; Pramono, Suwito Eko; Yulianto, Arief; Utomo, Cahyo Budi (Journal of Ecohumanism, 2025)
This study examined the mediating roles of academic adaptation and motivation in the relationship between self-efficacy and academic performance among seafaring students. A quantitative research design using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach was employed to analyze data collected from 284 Polytechnic Bumi Akpelni, selected from a population of 976 students across four maritime programs. Results revealed that while self-efficacy did not directly influence academic performance, it had a significant indirect effect through academic adaptation. Academic adaptation strongly mediated the relationship between self-efficacy and academic performance, whereas motivation, surprisingly, showed no significant mediating effect. The findings highlight the crucial role of adaptation capabilities in maritime education, suggesting that high self-efficacy primarily enhances academic performance by enabling better adaptation to the unique demands of maritime education. While this study provides valuable insights for maritime institutions in developing student support programs, its cross-sectional nature and single-institution focus suggest the need for longitudinal studies across multiple maritime institutions to better understand these relationships over time.